Synthesis and Characterization of Novel Schiff Bases of Imide Moiety - Hasan, Sulaiman M.; Samir, Ali H.; majeed, Ismaeel Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In our research novel schiff bases of imides moiety have been synthesized . Novel Schiff base derivatives of imides moiety have been synthesized by multistep reaction . First step involves prepare 2-amino -5-mercapto-1,3,4-thiadiazole (I) by the cyclization of thiosemicarbazide with carbon disulphide and anhydrous sodium carbonate in ethanol as a solvent . Then , compound (I) was  reacted with phthalic anhydride in the presence of glacial acetic acid to give 2-(5-mercapto-1,3,4-thiadiazol-2-yl) isoindoline-1,3-dion (II).Compound (II)was heated with ethyl chloracetate in the presence of potassium carbonatproduced ethyl 2(5-(1,3-dioxoisoindoline -2-yl)-1,3,4-thiadiazole-2-yl thio) acetate (III).The reaction of compound (III) with  hydrazine hydrate yielded 2-(5-(1,3-dioxoisoindoline -2-yl)-1,3,4thiadiazol-jm2-ylthio)acetohydrazide (IV).The fifth step involves reaction of compound (IV) with N,N-dimethyl aminobenzaldehyde to yield NÂ´-(4-(dimethyl amino)benzylidene )-2-(5(1,3-dioxoisoindoline-2-yl)-1,3,4-thiadiazole-2-yl-thio)acetohydrazide (V).The structures of the newly synthesized compounds were confirmed by physical properties and spectral (FTIR,1H-NMR)analysis